Pengaruh Green Marketing, Lifestyle, dan Environmental Awareness terhadap Brand Loyalty: Studi pada Pengguna Produk The Body Shop di Surabaya - Dinar Pramadhani; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In recent years, global issues regarding environmental problems have increased significantly. Humans are indirectly forced to continue to adapt and improve the quality of life to remain in line with the changes that occur. The concept of green marketing emerged as a response to issues of environmental damage. Green marketing helps businesses adopt more sustainable business practices because it helps promote the benefits of environmentally friendly products and services. The aim of this research is to determine the influence of green marketing, lifestyle, and environmental awareness on brand loyalty among users of The Body Shop products in Surabaya. The type of research used is quantitative research. The population in this study is all users of The Body Shop products who live in Surabaya, aged 17 years and over and with a history of purchasing at least twice using a sample of 200 respondents. The sampling method used is non-probability sampling, and the sampling technique is purposive sampling. Multiple linear regression analysis was applied to analyze the data tested with SPSS version 25. The results of this research state that green marketing, lifestyle, and environmental awareness have a significant effect on brand loyalty. The green marketing, lifestyle and environmental awareness variables are valid and reliable variables. Simultaneously, the variables green marketing, lifestyle and environmental awareness have a positive and significant effect on brand loyalty. Partially, the variables green marketing, lifestyle, and environmental awareness have a positive and significant effect on brand loyalty.